Hadith #4959 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan al-Nasa'i)
“Its price in those days was ten Dirhams.”
Grade:

Hadith #2392 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك (Sunan Abi Dawud)
(A man broke his fast intentionally) during Ramadan. The Messenger of Allah (ﷺ) commanded him to emancipate a slave, or fast for two months, or feed sixty poor men. He said: I cannot provide. The Messenger of Allah (ﷺ) said: Sit down. Thereafter a huge basket of dates (‘araq) was brought to the Messenger of Allah (ﷺ). He said: Take this and give it as sadaqah (alms). He said: Messenger of Allah, there is no poorer than I. The Messenger of Allah (ﷺ) thereupon laughed so that his canine
Grade: Sahih

Hadith #2950 - Sunan Abi Dawud - Harun bin Zayd bin Abi al-Zarqa' هارون بن زيد بن أبي الزرقاء التغلبي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
Malik ibn Aws ibn al-Hadthan said: One day Umar ibn al-Khattab mentioned the spoils of war and said: I am not more entitled to this spoil of war than you; and none of us is more entitled to it than another, except that we occupy our positions fixed by the Book of Allah, Who is Great and Glorious, and the division made by the Messenger of Allah (ﷺ), people being arranged according to their precedence in accepting Islam, the hardship they have endured their having children and their need.
Grade: Hasan

Hadith #3155 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ubada bin As-Samit (Sunan Abi Dawud)
Mus’ab b. ‘Umari was killed on the day of Uhud. He had only a striped cloak. When we covered his head with it, his feet appeared, and when we covered his feet, his head appeared. Thereupon the Messenger of Allah (ﷺ) said: Cover his head with it, and cover his feet with some grass.
Grade: Sahih

Hadith #4005 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
‘Abd Allah (b. Mas’ud) was told that the people had read this verse: “She said: Now come, thou” (hita laka). He said: I read it as I have been taught ; it is dearer to me. It goes “wa qalat haita laka” (She said: Now come thou).
Grade: Sahih

Hadith #4088 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد (Sunan Abi Dawud)
Mannan is the one takes account of anything he gives.
Grade: Sahih

Hadith #4417 - Sunan Abi Dawud - Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Waki' bin al-Jarrah وكيع بن الجراح; Yazid bin N'ym bin Hzal يزيد بن نعيم بن هزال الأسلمي (Sunan Abi Dawud)
The tradition mentioned above (No. 4401) has also been transmitted by Ubadah ibn as-Samit through a different chain of narrators. This version has: The people said to Sa’d ibn Ubadah: AbuThabit, the prescribed punishments have been revealed: if you find a man with your wife, what will you do? He said: I shall strike them with a sword so much that they become silent (i.e. die). Should I go and gather four witnesses? Until that (time) the need would be fulfilled. So they went away and gathered w
Grade: Da'if

Hadith #4447 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; ibn Umar; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The people passed by the Messenger of Allah (ﷺ) with a jew whose face blackened with charcoal and he was being taken around. He adjured them by Allah and asked: What is the prescribed punishment for a fornicator in your Divine book? He (the narrator) said: They referred him to a man of them. The Prophet (ﷺ) adjured him and asked: What is the punishment for a fornication in your Divine Book? He replied: Stoning. But fornication spread among our people of rank, so we disliked that a person of
Grade: Sahih

Hadith #4700 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Aslam Client Of 'Umar أسلم مولى عمر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Umar ibn al-Khattab; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
Son! You will not get the taste of the reality of faith until you know that what has come to you could not miss you, and that what has missed you could not come to you. I heard the Messenger of Allah (ﷺ) say: The first thing Allah created was the pen. He said to it: Write. It asked: What should I write, my Lord? He said: Write what was decreed about everything till the Last Hour comes. Son! I heard the Messenger of Allah (ﷺ) say : He who dies on something other than this does not belong to m
Grade: Sahih

Hadith #4880 - Sunan Abi Dawud - Abu Hurairah; Asbat bin Muhammad أسباط بن محمد; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Prophet (ﷺ) said: O community of people, who believed by their tongue, and belief did not enter their hearts, do not back-bite Muslims, and do not search for their faults, for if anyone searches for their faults, Allah will search for his fault, and if Allah searches for the fault of anyone, He disgraces him in his house.
Grade: Hasan Sahih

Hadith #4905 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Harun bin Zayd bin Abi al-Zarqa' هارون بن زيد بن أبي الزرقاء التغلبي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Umm al-Darda'a أم الدرداء; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
when a man cures anything, the curse goes up to heaven and the gates of heaven are locked against it. Then it comes down to the earth and its gates are locked against it. Then it goes right and left, and if it finds no place of entrance it returns to the thing which was cursed, and if it finds no place of entrance it returns to the thing which was cursed, and if it deserves what was said (it enters it), otherwise it returns to the one who uttered it. Abu Dawud said : Marwan b. Muhammad said: He
Grade: Hasan

Hadith #4961 - Sunan Abi Dawud - Aslam Client Of 'Umar أسلم مولى عمر; Harun bin Zayd bin Abi al-Zarqa' هارون بن زيد بن أبي الزرقاء التغلبي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Umar ibn al-Khattab; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The vilest names in Allah’s sight on the Day of resurrection will be that of a man called Malik al-Amlak. Abu Dawud said: This tradition has also been transmitted by Shu’aib b. Abi Hamzah from Abi al-Zinad through different chain of narrators. This version has the words “akhna’ ismin” (most obscene name) instead of “akhna ismin” (the vilest name).
Grade: Sahih

Hadith #4985 - Sunan Abi Dawud - Aisha bint Abi Bakr; Harun bin Zayd bin Abi al-Zarqa' هارون بن زيد بن أبي الزرقاء التغلبي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
Salim ibn AbulJa’dah said: A man said: (Mis’ar said: I think he was from the tribe of Khuza’ah): would that I had prayed, and got comfort. The people objected to him for it. Thereupon he said: I heard the Messenger of Allah (ﷺ) as saying: O Bilal, call iqamah for prayer: give us comfort by it.
Grade: Sahih

Hadith #5114 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Musa bin Mrwan موسى بن مروان; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
if a man becomes the client of any people without the permission of his patrons (i.e. those who have freed him), on him will be the curse of Allah, of angels and of all people; no obligatory or supererogatory worship will be accepted from him.
Grade: Sahih

Hadith #368 - Jami' al-Tirmidhi - Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; ibn Umar; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Nafie' نافع مولى ابن عمر; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
“I said to Bilal: ‘How did the Prophet (S) reply to them when they gave him Salams and he was performing Salat?’ He said: ‘He would motion with his hand.'”
Grade:

Hadith #765 - Jami' al-Tirmidhi - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sahl bin Sa'd bin Malik (Jami' al-Tirmidhi)
The Prophet said: “There is a gate in Paradise called Ar-Raiyyan, those who fast shall be invited into it, and whoever was among those who fasted, then he will enter it; and whoever enters it, he will never thirst again.”
Grade:

Hadith #1072 - Jami' al-Tirmidhi - Abdullah bin 'Amr bin al-'Aas; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Bashar Bindar محمد بن بشار بندار; Rabi'ya bin Syf bin Mat' ربيعة بن سيف بن ماتع; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي (Jami' al-Tirmidhi)
The Messenger of Allah said: “When a person dies, he is shown his place . If he is one of the people of Paradise; he is shown his place among the people of Paradise, and if he one of the people of the Fire; he is shown his place among the people of the Fire. Then it is said to him: ‘This is your place until Allah resurrects you on the Day of Judgment.'”
Grade:

Hadith #1614 - Jami' al-Tirmidhi - Abu Hurairah; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي (Jami' al-Tirmidhi)
From Jarir bin ‘Abdullah that the Messenger of Allah (ﷺ) sent a military expedition to Khath’am. So some people (living there) sought safety by prostrating, but they were met quickly and killed. News of this reached the Prophet (ﷺ) upon which he commanded that they be given half of the ‘Aql (blood money). And he said: “I am free from every Muslim that lives among the idolaters.” They said:”O Messenger of Allah: How is that ?” He said: “They should not see each other’s campf
Grade:

Hadith #1986 - Jami' al-Tirmidhi - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Jami' al-Tirmidhi)
“Indeed in Paradise there are chambers, whose outside can be seen from their inside, and their inside can be seen from their outside.” A Bedouin stood and said : ‘Who are they for, O Messenger of Allah?” He said: “For those who speak well, feed others, fast regularly, and perform salat during the night while the people sleep.”
Grade:

Hadith #3209 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abdullah bin 'Unays al-Juhani; al-Laith bin Sa'd الليث بن سعد; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Zayd bin 'Abdullah محمد بن زيد بن عبد الله بن عمر; Yonus bin Muhammad bin Muslim يونس بن محمد بن مسلم المؤدب (Jami' al-Tirmidhi)
“We called Zaid bin Harithah nothing but ‘Zaid bin Muhammad’ until the Qur’an was revealed (saying): ‘Call them by their fathers, that is more just according to Allah (33:5).'”
Grade:

Hadith #3272 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abu Hurairah; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Jami' al-Tirmidhi)
that Allah’s Prophet (ﷺ) said: “Jahannam will continue saying: ‘Are there any more’ until the Might Lord puts His Foot over it. It will say: ‘Enough! Enough! By Your Might.’ And one side of it will close in on the other.”
Grade:

Hadith #3274 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abu Hurairah; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Jami' al-Tirmidhi)
that Al-Harith bin Yazid Al-Bakri said: “I arrived in Al-Madinah and entered the Masjid and found it full with the people and I also noticed a black banner raised high, while Bilal was holding a sword before the Messenger of Allah (ﷺ). I said: ‘What is the matter with the people?’ They said: ‘He intends to send ‘Amr bin Al-‘As somewhere.'” So he mentioned the Hadith in its entirety, similar in meaning to the narration of Sufyan bin ‘Uyainah (#3273). He said: He is also called A
Grade:

Hadith #3944 - Jami' al-Tirmidhi - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Aslam Client Of 'Umar أسلم مولى عمر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Umar ibn al-Khattab; Zayd bin Aslam زيد بن أسلم (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) said: “Aslam, may Allah make them safe: Ghifar, may Allah forgive them, and ‘Usayyah has disobeyed Allah and His Messenger.”
Grade:

Hadith #1540 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ubada bin As-Samit; Yonus bin 'Abdul A'la al-Sadfi يونس بن عبد الأعلى بن ميسرة الصدفي (Sunan Ibn Majah)
the Messenger of Allah said: “The Sadaqah of Muslims should be taken at their watering places.”
Grade:

Hadith #1709 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Sahl bin Sa'd bin Malik (Sunan Ibn Majah)
“The Messenger of Allah said: ‘One of the best kinds of intercession is interceding between two people concerning marriage.”‘
Grade:

Hadith #1732 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu al-Darda; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Muhammad bin Bashar Bindar محمد بن بشار بندار; Umm al-Darda'a أم الدرداء (Sunan Ibn Majah)
“I heard the Messenger of Allah when he was on the pulpit, say: ‘Banu Hisham bin Mughirah asked me for permission to marry their daughter to ‘Ali bin Abu Talib, but I will not give them permission, and I will not give them permission, and I will not give them permission, unless ‘Ali bin Abu Talib wants to divorce my daughter and marry their daughter, for she is a part of me, and what bothers her bothers me, and what upsets her upsets me.”
Grade:

Hadith #2126 - Sunan Ibn Majah - Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin Waqid علي بن الحسين بن واقد المروزي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
he gave a horse in charity at the time of the Messenger of Allah (ﷺ), then he saw its owner selling it for a low price. He went to the Prophet (ﷺ) and asked him about that, and he said: “Do not buy what you gave in charity.”
Grade:

Hadith #2480 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aslam Client Of 'Umar أسلم مولى عمر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Umar ibn al-Khattab; Waki' bin al-Jarrah وكيع بن الجراح; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“It is disbelief for a man to attribute himself to someone other than his father knowingly, or to deny his connection to his father, even subtly.”*
Grade:

Hadith #2962 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Zayd bin 'Abdullah محمد بن زيد بن عبد الله بن عمر; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
It was narrated from Umm Sharik that the Prophet (ﷺ) told her to kill house lizards.
Grade:

Hadith #3063 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aslam Client Of 'Umar أسلم مولى عمر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ja'far bin Awn bin Ja'far جعفر بن عون بن جعفر; Umar ibn al-Khattab; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“O Allah, bless us in our city and in our fruits, in our Mudd and in our Sa’,* blessing upon blessing.” Then he would give it to the smallest of the children present.
Grade:

Hadith #3335 - Sunan Ibn Majah - Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; ibn Umar; Ma'n bin 'Isa bin Yahya معن بن عيسى بن يحيى; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade Al-Mufaddam.”
Grade:

Hadith #3451 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Ubaidullah bin 'Ali bin Abi Rafi' عبيد الله بن علي بن أبي رافع (Sunan Ibn Majah)
“When one of you gets up from his spot, then comes back, he has more right to it.”
Grade:

Hadith #4135 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Amr bin 'Uthman عمرو بن عثمان بن عفان; Asim bin 'Umar bin 'Uthman عاصم بن عمر بن عثمان; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘When Allah has saved the believers from Hell and they are safe, none of you will dispute with his companion more vehemently for some right of his in this world than the believers will dispute with their Lord on behalf of their brothers in faith who have entered Hell. They will say: ” Our Lord! They are our brothers, they used to pray with us, fast with us and perform Hajj with us, and you have admitted them to Hell.” He will say: “Go and bring forth
Grade:

Hadith #4156 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘No slave truly believes until he believes in four things: in Allah alone with no partner; that I am the Messenger of Allah; in the resurrection after death; and in the Divine Decree (Qadar).'”
Grade: